How Socio-Economic Status Contributes to Parents’ Views on English Teaching For Young Learners - Bambang Harmanto (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2018)
This study aims at identifying the contribution of parents’ socio-economic status (SES) toward their views on the teaching English for children. A survey technique with questionnaires and interviews was utilized to collect the data from 245 parents as the respondents. SPSS with Predictive Analysis Software (PASW) statistics 18 has been employed to analyze the collected data. Descriptively, the reseacher found that parents with different SES have showed similar beliefs on the importance of English mastery. They made acommitment to keep supporting their children with English. It was also found that although their knowledge on EYL was limited, their views and attitudes were good. Statistically, it showed that parents’ social and economic status either in their education, occupation, or income and their views on EYL were not significantly correlated. It came to the conclusion that parents today have equal vision in preparing their children with good education.